Pengaruh Budaya Organisasi, Pengembangan dan Pengawasan Terhadap Kinerja Karyawan pada Komisi Pemilihan Umum kota Probolinggo - Bahiyah, Khoridatil; Priantono, Seger; Hermawan, Dedi Joko (Fakultas Ekonomi dan Bisnis Universitas Panca Marga, 2025)
This study aims to determine the influence of organizational culture, development and supervision on employee performance at the Probolinggo City General Election Commission. The research method used is quantitative with a causal approach with independent variables, data collection techniques through interviews, questionnaires, and documentation. The sample of this study was employees at the Probolinggo City General Election Commission, with a total of 30 respondents. The results of the study indicate that organizational culture, development and supervision partially have a significant influence on employee performance at the Probolinggo City General Election Commission. A strong and positive organizational culture can improve employee performance, while effective development and supervision can help improve employee skills and knowledge. This study has implications that the Probolinggo City General Election Commission needs to pay attention to organizational culture, development and supervision to improve employee performance. In addition, this study also suggests that the Probolinggo City General Election Commission needs to conduct periodic evaluations to ensure that the organizational culture, development and supervision carried out are effective and efficient